Assisting students with argumentation plans when solving problems in CSCL - Monteserin, Ariel José (2010)
In CSCL systems, students who are solving problems in group have to negotiate with each other by exchanging proposals and arguments in order to resolve the conflicts and generate a shared solution. In this context, argument construction assistance is necessary to facilitate reaching to a consensus. This assistance is usually provided with isolated arguments by demand, but this does not offer students a real and integral view of the conflicts. In this work, we study the utilisation of argumentation plans to assist a student during the argumentation. The actions of an argumentation plan represent the arguments that a student might use during the argumentation process. Moreover, these plans can be integrated with the tasks needed to reach a shared solution. These plans give the student an integral and intuitive view of the problem resolution and the conflict that must be resolved. We evaluated our proposal with students of an Artificial Intelligence course. This evaluation was carried out by comparing three different assistance scenarios in which students had to solve exercises: no assistance, assistance with isolated arguments, and assistance with argumentation plans. The results obtained show that reaching consensus was easier for the students when the assistance was provided using argumentations plans.